Synthesis, characterizationand physiological activityof some novelisoxazoles - VINAYSINGH J. HUSHARE; PRITHVIRAJSINGH R. RAJPUT; MANOJKUMAR O. MALPANI; NITING G. GHODILE (Nusantara Bioscience, 2012)
Abstract. Hushare VJ, Rajput PR, Malpani MO, Ghodile NG. 2012. Synthesis, characterization and physiological activity of some novel isoxazoles. Nusantara Bioscience 4: 81-85. A series of chlorosubstituted 4-aroylisoxazoles have been synthesized by refluxing chlorosubstituted-3-aroylflavones and 3-alkoylchromone with hydroxylamine hydrochloride in dioxane medium containing 0.5 mL piperidine. Chlorosubstituted-3-aroylflavones and chlorosubstituted-3-alkoylchromone were prepared by refluxing them separately with iodine crystal in ethanol. Initially, chlorosubstituted-3-aroylflavanones and 3-alkoylchromanone were prepared by the interaction of different aromatic and aliphatic aldehydes with 1-(2’-hydroxy-3’,5’-dichlorophenyl)-3-phenyl-1,3-propanedione. Constitutions of synthesized compounds were confirmed on the basis of elemental analysis, molecular weight determination, UV-Visible, I.R., and 1H-NMR spectral data. The titled compounds were evaluated for their growth promoting activity on some flowering plants viz. Papaver rhoeas, Calendula officinalis, Gladiola tristis, Gaillardia aristata,  Dianthus chinensis, and Iberis sp. (candytuft). The results indicate that applicated plants had higher shoots and number of leaves.